A coupled electromagnetic-thermal-fluid-kinetic model for microwave-assisted production of Palm Fatty Acid Distillate biodiesel - Yeong, S.; Law, Ming; You, K.; Chan, Y.; Lee, V. (Elsevier, 2019)
© 2019 Elsevier Ltd The production of biodiesel using alternative feedstocks and green technologies has attracted increasing interest of researchers worldwide. In this study, the production of biodiesel through microwave-assisted esterification of Palm Fatty Acid Distillate (PFAD) was studied experimentally as well by means of a simulation. The complex permittivities of PFAD and biodiesel were experimentally measured for the temperature range 25–120 °C. At the microwave frequency of 2.45 GHz, the dielectric properties of PFAD and its biodiesel were found to be 2.78–0.17j and 3.26–0.21j respectively. An optimal biodiesel yield (91.88%) was reported at 15 min of 300 W microwave irradiation, for a 1:9 PFAD to methanol ratio catalysed by sulfuric acid. The study revealed that microwave-assisted PFAD esterification has a second order reaction kinetics, with a frequency factor of 3.65 × 10-8 M-1 s-1 and an activation energy of -36 kJ. For the first time, a three-dimensional multi-physics model was developed for the microwave-assisted PFAD esterification process in this study. The simulated model included the effects of electromagnetic propagation, heat transfer, fluid flow, and chemical species conservation. The numerical predictions were found to be in good agreement with the experimental results. The study also found that the fluid flow and vaporisation of methanol and water are important for good model prediction.